Anastomotic Leakage and Chronic Presacral Sinus Formation After Low Anterior Resection: Results From a Large Cross-sectional Study. Issue 5 (November 2017) - Borstlap, Wernard A. A.; Westerduin, Emma; Aukema, Tjeerd S.; Bemelman, Willem A.; Tanis, Pieter J.
Abstract : Objectives: Little is known about late detected anastomotic leakage after low anterior resection for rectal cancer, and the proportion of leakages that develops into a chronic presacral sinus. Methods: In this collaborative snapshot research project, data from registered rectal cancer resections in the Dutch Surgical Colorectal Audit in 2011 were extended with additional treatment and long-term outcome data. Independent predictors for anastomotic leakage were determined using a binary logistic model. Results: A total of 71 out of the potential 94 hospitals participated. From the 2095 registered patients, 998 underwent a low anterior resection, of whom 88.8% received any form of neoadjuvant therapy. Median follow-up was 43 months (interquartile range 35–47). Anastomotic leakage was diagnosed in 13.4% within 30 days, which increased to 20.0% (200/998) beyond 30 days. Nonhealing of the leakage at 12 months was 48%, resulting in an overall proportion of chronic presacral sinus of 9.5%. Independent predictors for anastomotic leakage at any time during follow-up were neoadjuvant therapy (odds ratio 2.85; 95% confidence interval 1.00–8.11) and a distal (⩽3 cm from the anorectal junction on magnetic resonance imaging) tumor location (odds ratio 1.88; 95% confidence interval 1.02–3.46). Conclusions: This cross-sectional study of low anterior resection for rectal cancer in the Netherlands in 2011, with almost routine use of neoadjuvant radiotherapy, shows that one third of anastomotic leakages is diagnosed beyond 30 days, and almost half of the leakages eventually do not heal. Chronic presacral sinus is a significant clinical problem that deserves more attention. Abstract : Supplemental Digital Content is available in the text